Node adaptive sleeping mechanism of DCF protocol in ad hoc networks - LEI Lei; XU Zong-ze; LIU Xu (Tongxin xuebao)
Most of the existing node sleeping mechanisms in ad hoc networks adopt the PA/RT （periodically awake with reserve transmission） strategy, however, this strategy has some shortcomings. To overcome these shortcomings, a node adaptive sleeping mechanism （NASM） of DCF protocol was presented which can be used on both single-hop and multi-hop ad hoc networks. This sleeping mechanism does not rely on the PA/RT strategy, and permits the node to adaptively adjust the length of sleeping time according to the communication status of the nodes. The simulation results show that NASM can effectively save the average energy consumption of the nodes without significantly impairing the other performance indexes of the network.